2003
DOI: 10.1021/ie0301029
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution and Morphology of in Situ Suspension Polymerized Toner

Abstract: A spherical polymerized toner with an average size around 10 µm and a span (D 0.9 -D 0.1 )/D 0.5 of 1.5-2.0 is prepared directly by in situ suspension copolymerization of a mixture of styrene/ n-butyl acrylate/iron black. The particle size distribution (PSD) and morphological properties of the toner are investigated. On the basis of the analysis of droplet breakage, coalescence, and growth in the preparation of the polymerized toner, several factors affecting the droplet size, PSD, and morphology of the toner,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…According to Table III, most of the span data show values in the range between 1.15 and 1.55, which, being lower than 2, allows the PSDs to be considered narrow. 50 Other authors have reported PSDs of microparticles obtained by suspension polymerization techniques that are not as narrow as those reported here and also with an average size larger than in this work. 32,[51][52][53] Moreover, because those works did not provide any images of the product, it is not possible to know whether the PSDs of their polymeric product were reflecting individual microparticles or clusters of microparticles.…”
Section: Breadth Of Psd Analysissupporting
confidence: 50%
See 1 more Smart Citation
“…According to Table III, most of the span data show values in the range between 1.15 and 1.55, which, being lower than 2, allows the PSDs to be considered narrow. 50 Other authors have reported PSDs of microparticles obtained by suspension polymerization techniques that are not as narrow as those reported here and also with an average size larger than in this work. 32,[51][52][53] Moreover, because those works did not provide any images of the product, it is not possible to know whether the PSDs of their polymeric product were reflecting individual microparticles or clusters of microparticles.…”
Section: Breadth Of Psd Analysissupporting
confidence: 50%
“…By using a set of suitable synthesis conditions, with which it was possible to obtain polymeric microbeads with optimum values of their morphological characteristics, a study was made of the effect of the geometric factors of the experimental device on (a) the morphological characteristics of the microparticles, designated as agglomeration and sphericity indices and (b) the mean (d 50 ) and breadth (span) of the PSD. The research was first planned through a factorial design of experiments, and, upon analyzing the results obtained for the agglomeration and sphericity indices, it may concluded that the stability of dispersion was achieved in all the experiments despite changing the magnitudes of the geometric factors and keeping the values of the synthesis conditions constant.…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters affecting droplet size, particle size and distribution, morphology of the toner, i.e., agitation speed, ultrasonic introduction, addition of different types and amounts of surfactants play a key role in microemulsion as compared to emulsion or suspension polymerization [28]. Stable emulsions were…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…Strene (St) is a conventional monomer for radical polymerizations and PSt has been widely used to encapsulate pigment particles4, 7, 14, 15 because of its merits of cheap and anticorrosion. With its hydrophobic property, St is particularly suitable for suspension polymerization method.…”
Section: Introductionmentioning
confidence: 99%